TOOLS AND METHODS FOR THE DEVELOPMENT OF PHYSICAL FITNESS OF PRIMARY SCHOOL STUDENTS - Pulatova Yulduz Shuxratovna (Web of Journals Publishing, 2023)
Many scientific research works are being carried out in world countries to organize extracurricular activities, to form skills and competencies related to movement and to develop physical qualities in order to meaningfully spend students' free time and strengthen their health. Current data indicate that the movement activity of students of the middle lane of education is declining. The main reasons for such a situation are explained by foreign specialists in the absence of motivation for physical education activities in schoolchildren, methodological approaches to organizing the educational process, insufficient research of the means and methods of physical training. In order to educate students who meet modern requirements, physical education requires the search for new tools and methods of using extracurricular forms of activity.
Keywords: physical fitness, sports, physical qualities, physical activity, loads, standard loads, strength.